(untitled) (Innovative professional education, 2025)
The article emphasizes the importance of integrating digital technologies into the educational process and demonstrates how GeoGebra can contribute to a deeper understanding of mathematics among students in vocational education institutions. Practical examples of using GeoGebra for solving equations, analyzing geometric figures, and conducting statistical research are provided.